The bioactive properties of Spirulina-derived phycobiliproteins and phycobilins - Minić, Simeon (Biologia Serbica, 2021)
Arthrospira (Spirulina), a photosynthetic, filamentous cyanobacteria, has been used as a food for centuries. It is one of the richest known natural sources of protein and essential amino acids, as well as an excellent source of vitamins, macro-and micro-elements, pigments, essential fatty acids, glycolipids, and polysaccharides. Cphycocyanin (C-PC), the most abundant protein in Spirulina, is a highly fluorescent and water-soluble heterodimeric phycobiliprotein. Its blue colour arises from a covalently attached (via a thioether bond) tetrapyrrole chromophore, phycocyanobilin (PCB). Numerous studies have shown that C-PC exhibits significant anti-inflammatory, immunomodulatory and anticancer effects which could be ascribed to the powerful anti-oxidative activities of PCB. In fact, investigation of C-PC digestion in simulated gastrointestinal conditions has shown that the resulting chromopeptides possess significant anticancer, anti-oxidative and metal-binding properties. Furthermore, it has been shown that various proteins (human and bovine serum albumins, bovine catalase, bovine lactoglobulin) can bind PCB, which could influence the pharmacokinetic behaviour, bioavailability and oxidative stability of PCB. On the other hand, the presence of tetrapyrrole chromophore increases the thermal, oxidative and digestion stability of these proteins. This work reviews recent findings on the bioavailability, distribution and bioactive properties of C-PC and its chromophore, with an emphasis on their fundamental significance and potential applications.